Quality of working life and organizational performance – two sides of the same coin? - Pot, Frank D; Koningsveld, Ernst AP (Scandinavian Journal of Work, Environment & Health, 2009)
' ' OBJECTIVE ': 'This discussion paper presents the debate on the theoretical and practical claim that a simultaneous improvement in the quality of working life and organizational performance can be achieved by workplace development. ' ' METHODS ': 'We discuss theories that support this claim or could provide additional support, and mention six “programs” on workplace development or social innovation in European countries. We present the results of evaluation studies in Finland, Germany, Ireland, and the Netherlands. ' ' RESULTS ': 'A correlation of 0.50 was found between the quality of working life and organizational performance. All evaluations showed that the simultaneous improvement in the quality of working life and performance was achieved in a number of, but not all, projects. The percentage of successful projects is not always clear and depends on which aspects of quality of working life and performance were taken into account. Our estimation would be 25–50%. Which factors are important for success? With the exception of the commitment of top management and employee participation, other determinants were difficult to distinguish due to differences in research designs and programs. ' ' CONCLUSIONS ': 'Important issues for discussion remain with respect to theory, research and practical approaches. Research should be more concerned with patterns of independent variables and how organizations deal with dilemmas. The most important pitfall appears to be taking a top-down as opposed to participatory approach involving employees and their supervisors in projects. National programs seem to be more effective than the initiatives of separate stakeholders groups.
Keywords: discussion paper; organizational performance; quality; social innovation; working life; worklife; workplace development